Auditing Good Government in Africa : public sector reform, professional norms and the development discourse - Gustavson, Maria, 1977- (Hampshire : Palgrave Macmillan, 2014)
"The inability of many democratic governments in Africa to govern effectively has been an important factor in the many problems that the continent and its constituent countries have faced over the past decades. The question for scholars has been in learning what has caused the endemic failure of public institutions throughout Africa and understanding how to create good government in the future of the continent. Strongly supported by empirical evidence, this book challenges the existing literature on the subject by breaking with the traditional notion among academics that the key to good government in Africa is through the creation of unique administrative structures, or at the very least developing significantly adapted foreign structures with an emphasis on the specific structure of African societies. Instead the author contrasts this notion with theories from other research fields suggesting that public officials are likely to be interested in following professional norms and that organizations generally strive to imitate each other, regardless of geographical location. This book presents rich original empirical research from the field of state audit in Sub-Saharan Africa where the above different theoretical approaches are empirically explored. The research results contradict many assumptions made in the literature on development and points to the importance of adding other dimensions, such as professional norms, to nuance the discussion of the future of the African continent. "--
Includes bibliographical references and index.
Keywords: Public administration -- Africa, Sub-Saharan -- Evaluation; Civil service reform -- Africa, Sub-Saharan.; Administrative agencies -- Africa, Sub-Saharan -- Management -- Evaluation; Public officers -- Professional ethics -- Africa, Sub-Saharan.; Political culture -- Africa, Sub-Saharan.; Political science / Political Ideologies / Democracy; Political science / History & Theory; Political science / Political Process / General; Political science / Public Affairs & Administration; Political science / Government / National; Africa, Sub-Saharan -- Politics and government -- 21st century